Real‐Time Study on Structure Formation and the Intercalation Process of Polymer: Fullerene Bulk Heterojunction Thin Films. Issue 3 (24th January 2020) - Kassar, Thaer; Berlinghof, Marvin; Güldal, Nusret Sena; Schmutzler, Tilo; Zontone, Federico; Brandl, Marco; Metwalli, Ezzeldin; Will, Johannes; Li, Ning; Ameri, Tayebeh; Brabec, Christoph J.; Unruh, Tobias
Abstract : Fullerene intercalation between the side chains of conjugated polymers has a detrimental impact on both charge separation and charge transport processes in bulk heterojunction (BHJ) organic photovoltaic cells (OPVs). In situ grazing incidence X‐ray scattering experiments allow to characterize the structure formation, drying kinetics, and intercalation in blends of phenyl‐c61‐butyric acid methyl ester (PC60 BM) and poly(2, 5‐bis(3‐tetradecylthiophen‐2‐yl)thieno[3, 2‐b]thiophene) named (pBTTT‐C14) from their 1, 2‐orthodichlorobenzene (oDCB) solutions with different volume fractions of dodecanoic acid methyl ester (Me12) as a solvent additive. The structure formation process during evaporation of the solvent:additive mixture can be described by five periods, which are correlated to a multistep contraction of the lamellar stacking of the bimolecular crystals. The onset of crystallization is delayed by increasing the additive volume fraction in the coating solution leading to a promoted crystallinity. A conclusive picture of fullerene intercalation and additive‐tuned structural evolution during the drying of thin films of the polymer:fullerene BHJ blends will be presented. Abstract : Real‐time grazing incidence X‐ray scattering measurements show that the additive‐tuned film formation of intercalating polymer:fullerene bulk heterojunction (BHJ) blends subdivides into five periods, which correspond to a multistep contraction of the lamellar stacking of the polymer chains.